Adaptive UAV - Poh, Yze Yang. (2013)
An adaptive UAV is able to adapt to the conditions it is operating in. Many UAVs utilizes unique recovery techniques to adapt to their respective landing constraints. The recovery space is usually minimal for military UAVs or UAVs operating in harsh conditions. In this study, a parafoil-fixed wing hybrid system is proposed for landing to cater for a small landing area. Both the parafoil and fixed wing platform are successful in their respective and independent developments. Their operation advantages are thus combined into a single adaptive UAV concept. The aircraft flies with the parafoil on its belly and upon requirement, deploys the parafoil over itself to transit to parafoil flight. Numerous progressive experiments have been conducted alongside computer simulations and computer aided design (CAD). Flight data have been recorded for post flight analysis through sensors and avionics to understand the flight dynamics at the various stages of transition. The study uses a design, fabricate and test cycle in order to achieve the objectives with the various prototypes proposed. Practical problems are encountered and resolved through theory which eventually verifies with experiment. With the proposed solutions applied, the final results are positive and the concept is feasible.